Characterization of Vibrio fluvialis qnrVC5 Gene in Native and Heterologous Hosts: Synergy of qnrVC5 with other Determinants in Conferring Quinolone Resistance - Vinothkumar, Kittappa; Kumar, G. N.; Bhardwaj, Ashima K. (Frontiers in Microbiology, 2016)
Resistance of various pathogens towards quinolones has emerged as a serious threat to combat infections. Analysis of plethora of genes and resistance mechanisms associated with quinolone resistance reveals chromosome-borne and transferable determinants. qnr genes have been found to be responsible for transferable quinolone resistance. In the present work, a new allele qnrVC5 earlier reported in Vibrio fluvialis from this laboratory was characterized in detail for its sequence, genetic context and propensity to decrease the susceptibility for quinolones. The study has revealed persistence of qnrVC5 in clinical isolates of V. fluvialis from Kolkata region through the years 2002 to 2006. qnrVC5 existed in the form of a gene cassette with the open reading frame being flanked by an upstream promoter and a downstream V. cholerae repeat region suggestive of its superintegron origin. Sequence analysis of different qnrVC alleles showed that qnrVC5 was closely related to qnrVC2 and qnrVC4 and these alleles were associated with V. cholerae repeats. In contrast, qnrVC1, qnrVC3 and qnrVC6 belonging to another group were associated with V. parahaemolyticus repeats. The gene manifested its activity in native V. fluvialis host as well as in E. coli transformants harbouring it by elevating the MIC towards various quinolones by 2- to 8-fold. In combination with other quinolone resistance factors such as topoisomerase mutations and aac(6’)-Ib-cr gene, qnrVC5 gene product contributed towards higher quinolone resistance displayed by V. fluvialis isolates. Silencing of the gene using antisense peptide nucleic acid sensitized the V. fluvialis parent isolates towards ciprofloxacin. Recombinant QnrVC5 vividly demonstrated its role in conferring quinolone resistance. qnrVC5 gene, its synergistic effect and global dissemination should be perceived as a menace for quinolone-based therapies.